Alfie Green and the Conker King - O'Brien, Joe; Illustrated by Texier, Jean (Dublin O'Brien, 2007)
It's time for the Budsville Primary School Conker Championship, and Alfie needs to find a special conker. Alfie Green Book 6
Include Illustration
Keywords: Magic -- Conkers (Game)